CORRELATING WRITER’S BLOCK AND ESL LEARNERS’ WRITING QUALITY - Dela Rosa, John Paul O.; Genuino, Cecilia F. (Indonesian Journal of Applied Linguistics, 2018)
Despite the importance of writing in the language learners’ development, there are difficulties faced by English as a Second Language (ESL) learners that stem from various factors. One of them is the presence of writer’s block that could affect writing quality. Therefore, this study aims to describe writer’s block, along with a statistically-laden analysis of the possible correlation between the blocking experiences of 55 Filipino ESL learners and the levels of easability and readability of the essays they had written.  This research employed a descriptive-correlational design using The Questionnaire in Identifying Writer’s Block (QIWB) to gauge the extent of occurrence of writer’s block and the Coh-Metrix Common Core Text Easability and Readability Assessor (hereafter Coh-Metrix T.E.R.A.), an online computational tool, to measure the levels of easability and readability of the essays. The result shows that the learners generally experienced writer’s block, and their essays collectively showed high levels of easability on the basis of narrativity, referential cohesion, and deep cohesion. However, the essays were low in syntactic simplicity and word concreteness, while the level of readability computed exceeded that of the reading ability of 10th-grade learners. Test of correlation revealed that there exists negligible relationship between writer’s block and the overall easability and readability levels of the essays, though a significant but a weak relationship was documented between lateness and word concreteness and with premature editing and deep cohesion, respectively.